Konsepsi Keruangan Multipihak dalam Pembangunan Infrastruktur Jalan Lingkar Kota di Lhokseumawe - Putri Ananda Saka; Setiadi Setiadi (Jurnal Community, 2022)
The urban ring road infrastructure as a development project designed to improve accessibility as well as mobility is in fact inseparable from problems that lead to the disruption of development continuity. One important issue that also affects the sustainability of development is spatial issues. Development is carried out on freed community land and this has relevance to how land as space is viewed. For this reason, this research aims to reveal differences in spatial perspectives among development stakeholders and formulate them as causes for the failure of development. Through a qualitative approach and borrowing Henri Lefebvre's spatial perspective, this research reveals that there are different perspectives among local communities, local governments, city governments and road users regarding the ringroad development. Local community tend to view development areas as areas that are close to their lives so that there is no shared awareness of the importance of road construction, in contrast to road users who prioritize the principles of effectiveness and comfort. Meanwhile, the village government sees the road as part of tourism project, while the city government views it as a state asset that will open up new accessibility spaces. This difference in spatial perspective creates an inconsistency of perspective among development actors which in the end has an impact on the neglect of development.